Magnesium-enriched hydroxyapatite at immediate implants: a histomorphometric study in dogs - Caneva, Marco [UNESP]; Botticelli, Daniele; Stellini, Edoardo; Scombatti Souza, Sergio Luis; Salata, Luiz Antonio; Lang, Niklaus P. (Wiley-Blackwell, 2011)
AimTo evaluate the influence of magnesium-enriched hydroxyapatite (MHA) (SintLife (R)) on bone contour preservation and osseointegration at implants placed immediately into extraction sockets.Material and methodsIn the mandibular pre-molar region, implants were installed immediately into extraction sockets of six Labrador dogs. MHA was placed at test sites, while the control sites did not receive augmentation materials. Implants were intended to heal in a submerged mode. After 4 months of healing, the animals were sacrificed, and ground sections were obtained for histomorphometric evaluation.ResultsAfter 4 months of healing, one control implant was not integrated leaving n=5 test and control implants for evaluation. Both at the test and the control sites, bone resorption occurred. While the most coronal bone-to-implant contact was similar between test and control sites, the alveolar bony crest outline was maintained to a higher degree at the buccal aspect of the test sites (loss: 0.7 mm) compared with the control sites (loss: 1.2 mm), even though this difference did not reach statistical significance.ConclusionsThe use of MHA to fill the defect around implants placed into the alveolus immediately after tooth extraction did not contribute significantly to the maintenance of the contours of the buccal alveolar bone crest.To cite this article:Caneva M, Botticelli D, Stellini E, Souza SLS, Salata LA, Lang NP. Magnesium-enriched hydroxyapatite at immediate implants: a histomorphometric study in dogs.Clin. Oral Impl. Res. 22, 2011; 512-517doi: 10.1111/j.1600-0501.2010.02040.x.
Keywords: animal study; bone healing; extraction socket; implant dentistry; osseointegration; regeneration; ridge preservation